El mapa de susceptibilidad a movimientos en masa: una herramienta para la gestión sostenible del territorio - Obregón, Christian (2013)
This study aims to show the importance of Landslide Susceptibility Map as a tool for land use planning, prevention and risk mitigation. This will be shown through MM evaluation processes affecting high sector of El Paraíso gorge - Villa María del Triunfo (Lima - Peru).The work consisted of two phases: in the first one (field) the intrinsic characteristics of geology and geomorphology were identified. The second one, included the Landslide Susceptibility Map generation, using the multivariate Heuristic Model consisting of overlapping maps variables (Carrara et al. 1995, Lain et al. 2005), developed in a GIS environment through algebra layer (geoprocessing operations).The results of Landslide Susceptibility Map in general, give us geoscience information that will contribute to land management, and in a timely manner, with the development of specific studies, prevention and / or mitigation measures to ensure the physical stability of identified critical areas.